Potency of fibraurea tinctora lour. extract as anti-bacterial agents towards pathogenic bacteria - Zalizar, Lili; Rahayu, Imbang Dwi; ,, Sujono; Ahmad Nor, Yusilawati (Institute of Physics Publishing, 2019)
This research aimed to explore antibacterial activity of Fibraurea tinctora Lour. extracted by ethanol and hot water. The treatments of study consisted of six levels of F. tinctora plant extract (0 %, 0.625 %, 1.25 %, 2.50 %, 5.00 % and 10.0 %, respectively) either using ethanol or hot water, resulting in 12 experimental treatments according to 6 × 2 factorial arrangement in a completely randomized design. Each of the treatment was replicated three times. Results of this research showed that either ethanol or hot water F. tinctora extract have potency to control farm pathogenic bacteria. In the lowest concentration (0.625 %) both extract significantly inhibited bacteria growth (Minimum Inhibition Concentration). The highest antibacterial activity was in group that had the highest concentration (10 %) of extract in both of the bacteria. Staphylococcus aureus were more susceptible to the F. tinctora extract than Escherichia coli. Result from spectrophotometry UV-vis assessments showed that the total composition of tannin, alkaloid, and saponin from ethanol extract of F. tinctoria is higher than its water based extract. Meanwhile, phenol composition of water-based extract from F. tinctoria is higher than from ethanol extract. Keywords: Antibacterial, bioactive compounds, herbal medicine, natural yellow root